RETRACTED: PRDM16 Upregulation Induced by MicroRNA-448 Inhibition Alleviates Atherosclerosis via the TGF-β Signaling Pathway Inactivation - Liu, Dongxing; Song, Jiantao; Ji, Xianfei; Liu, Zunqi; Li, Tao; Hu, Bo (Frontiers in Physiology, 2020)
The dysregulated expression of microRNAs (miRs) has been associated with pathological and physiological processes of atherosclerosis (AS). In addition, PR domain-containing 16 (PRDM16), a transcriptional mediator of brown fat cell identity and smooth muscle cell activities, may be involved in the hypercholesterolaemia during development of AS. The bioinformatic analysis identified a regulatory miR-448 of PRDM16. Hence, the current study aimed to explore whether miR-448 influenced the activities of aortic smooth muscle cell (ASMCs) in AS. We validated that miR-448 was highly expressed in peripheral blood of patients with AS and aortic smooth muscle of AS model mice. Whereas, PRDM16 was downregulated in the aortic smooth muscle of AS model mice. PRDM16 overexpression was observed to inhibit oxidative stress injury and cell proliferation, and promote apoptosis of ASMCs. Mechanistic studies revealed that miR-448 targeted PRDM16 and negatively regulated the PRDM16 expression, while PRDM16 blocked the TGF-β signaling pathway. Furthermore, Downregulated miR-448 alleviated oxidative stress injury, and attenuated ASMC cell proliferation, migration and enhanced cell apoptosis through upregulation of PRDM16. Taken together, silencing of miR-448 upregulates PRDM16 and inactivates the TGF-β signaling pathway, thereby impeding development of AS by repressing the proliferation, migration and invasion of ASMCs.